Sino-Australian University Partnership in Health Management Education - Leggat, Sandra G.; Liu, Chaojie; Wu, Qunhong (Frontiers in Public Health, 2018)
This paper outlines a successful partnership program between La Trobe University in Melbourne Australia and Harbin Medical University in Harbin, China. These two universities have been collaborating for more than 15 years to provide a comprehensive Master of Health Administration program that adapts the Australian curriculum to meet the rapidly increasing need for qualified health services managers throughout China. This paper describes the mechanisms by which the joint programs were developed and how the two universities work together in partnership to continually improve the program components and outcomes, taking into account the significant differences in context and cultures. Since 2001, La Trobe University has enrolled about 1000 Chinese health services managers, with 721 completing a Master’s degree, who are now having increasing influence on the reforms of the Chinese health care system. The partnership has enriched Australian knowledge of Chinese culture and values, as well as the Chinese health system and health policies, as evidenced by the large volume of joint publications. The profession of health management has been substantially strengthened in China, and working together, Chinese and Australian academics have had demonstrated impact on enhancing the reforms of the Chinese public health system. Further studies, with sufficient funds for data collection, are needed to evaluate the long-term impacts of transnational programs on academic and health system development in China.